Mesenteric lymph drainage alleviates hemorrhagic shock-induced spleen injury and inflammation - Zhang,Hong (2019)
Abstract Purpose: To investigate the effect of mesenteric lymph drainage on the spleen injury and the expressions of inflammatory cytokines in splenic tissue in mice following hemorrhagic shock. Methods: Male C57 mice were randomly divided into the sham shock, shock and shock+drainage groups. The mice in both shock and shock+drainage groups suffered femoral artery bleeding, maintained mean arterial pressure (MAP) of 40±2 mmHg for 90 min, and were resuscitated. And mesenteric lymph drainage was performed in the shock+drainage group at the time of resuscitation. After three hours of resuscitation, the splenic tissues were harvested for the histological observation and protein and mRNA expression analysis of cytokines. Results: The spleen in the shock group revealed a significantly structural damage and increased mRNA expressions of MyD88 and TRAF6 and protein expressions of TIPE2, MyD88, TRIF and TRAF3 compared to the sham group. By contrast, the splenic pathological injury in the shock+drainage group was alleviated significantly, and the mRNA and protein expressions of TIPE2, MyD88, TRIF, TRAF3 and TRAF6 were significantly lower than those in the shock group. Conclusion: These results indicate that post-hemorrhagic shock mesenteric lymph drainage alleviates hemorrhagic shock-induced spleen injury and the expressions of inflammatory cytokines.